1981
DOI: 10.3133/pp1179
|View full text |Cite
|
Sign up to set email alerts
|

Systematic ice retreat in New England

Abstract: The mode of ice retreat after the maximum advance of the Wisconsinan glacier that last covered New England has been a subject of controversy for more than 100 years. Two major opposing views dur ing most of this period focused on whether recession was characterized by systematic retreat of active glacier ice or by regional stagnation. Difficulty in correlating with the well-established ice-recessional history in the Middle West hampered the discussion in New England. In the last few decades, detailed mapping o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The application of the morphosequence concept in central to southern New England (Koteff and Pessl, 1981) showed that systematic ice-margin retreat occurred in many areas where end moraines are scarce or absent. This paradigm shift forced a reevaluation of the stagnation theory throughout the region.…”
Section: Introductionmentioning
confidence: 99%
“…The application of the morphosequence concept in central to southern New England (Koteff and Pessl, 1981) showed that systematic ice-margin retreat occurred in many areas where end moraines are scarce or absent. This paradigm shift forced a reevaluation of the stagnation theory throughout the region.…”
Section: Introductionmentioning
confidence: 99%
“…In the area described by Thompson, ice flow shifts to the south/southwest, indicating that there may have been an active ice tongue flowing towards the Stony Brook drainage in the Puzzle Mountain quadrangle to the west. In areas that lack abundant moraines such as the Western Maine Mountains, the direction of ice retreat may also be tracked by the location of meltwater channels and sediments deposited by glacial meltwater (morphosequences) (Koteff and Pessl, 1981). Basal radiocarbon ages from ponds in western Maine indicate that the East Andover quandrangle was deglaciated between 13,200 and 12,300 radiocarbon years BP (Borns and others, 2004).…”
Section: Spigel Whittaker and Gordonmentioning
confidence: 99%
“…In the area described by Thompson, ice flow shifts to the south/southwest, indicating that there may have been an active ice tongue flowing towards the Stony Brook drainage in the Puzzle Mountain quadrangle to the west. In areas that lack abundant moraines such as the Western Maine Mountains, the direction of ice retreat may also be tracked by the location of meltwater channels (Thompson, 2001) and sediments deposited by glacial meltwater (morphosequences) (Koteff and Pessl, 1981). Basal radiocarbon ages from ponds in western Maine indicate that the East Andover quandrangle was deglaciated between 13,200 and 12,300 radiocarbon years BP (Borns and others, 2004).…”
Section: Surficial Geology Previous Observations and Researchmentioning
confidence: 99%